MORPHOMETRIC AND SCANNING ELECTRON MICROSCOPE-BASED IDENTIFICATION OF Taenia hydatigena PARASITES IN STRAY DOGS - GH. D. Al-Sudani; A. M. A. Al-Amery (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Taenia hydatigena, an intestinal parasite of domestic and wild canids which can cause medical problems and economic losses in animals. Thirty T. hydatigena recovered from the intestine of stray dogs after T. hydatigena based on morphological characters and morphometric observations involving Scanning Electron Microscopy (SEM) and the scoleces were stained by Semichon’s acid carmine and viewed on a light microscope. High-quality SEM photographs were shown the blade dimensions of both large and small hooks (83.89 µm and 48.16 µm) respectively, which was close to measurements by a digital camera. The number of hooks around the rostellum were 30 hooks, and both were equal in number (15 hooks), while the average length of the large hooks was 220.11 ±28.07 µm, and was 88.58 ±7.92, and the average length of small hooks was142.37 ±12.52 µm and was 65.73 ±6.94 µm. body surface of Taenia hydatigena presence of characteristic transverse cuticular striations.